Sanitary condition and hygienic practice of street food vendors in selected towns of Ethiopia: A cross-sectional study addressing public health concern - Mathewos Moges; Ernest Kristian Rodland; Ambelu Argaw (Journal of Agriculture and Food Research, 2024)
Background: Street foods are ready-to-eat foods prepared and/or sold by vendors and hawkers in public places such as streets and plazas. Despite being widely available and affordable, they pose a significant public health risk. Objective: This study aims to assess the hygienic practices of street food vendors, sanitary condition of their stalls and associated factors in selected towns of Ethiopia. Method: Community-based Cross-sectional study design was used from December 2022 to January 2023 in Addis Ababa, Dire Dawa, Hawassa, and Jimma towns of Ethiopia. A total of 1168 street food-vending stalls were determined using a single population proportion formula. Proportional allocation to the total population of the towns was used to assign the number of street food vending stalls to each town and sub cities. The interviewer-administered questionnaire and an observational checklist were used to collect data. Bivariate and multivariate analyses were run using statistical Package for Social Sceinces (SPSS) V-23. Result: The study included 926 street food vendors from Addis Ababa, 84 from Dire Dawa, 99 from Hawassa, and 59 from Jimma. The majority of respondents (86%) were female, with a mean age of 31.26. 60% of respondents were married, and 57% had completed primary school. 18% of street food vendors prepared their food on the street, with no shelter or shade. The overall good hygienic practices of the street food vendors were 16% while the good sanitary status of the vending stalls was 6.8 %. Sex, work experience, receiving training on food safety, having medical checkup, availability of hand washing facilities, and having good knowledge on food safety were predictors of good hygienic practice. Conclusion: Most of the street food vendors had poor hygienic practices as well as their vending stalls had poor sanitary conditions. Hence, encouragement and support for street food vendors to have improved water, sanitation, and hygiene facilities in the vicinity, along with strict regulations, will help the vendors provide safe food to consumers, thereby protecting the public's health.